Research on vibration mechanism and control technology of building structure under earthquake action - Gu, Hongyan; Liang, Huimin; Tong, Guoyun; Liu, Fang; Liu, Yu; Liu, Xing; Jia, Zhen; Paul, John (JVE International, 2021)
The large engineering building structures are costly and thus complex to maintain due to their chances of failure under various hazardous conditions. These buildings are needed to be protected against the damage due to the hazards like earthquake, wind, seismic waves, etc. This article focuses on the investigation of vibration mechanism and control strategies for protection of buildings from the hazardous situations. The article presents a robust solution of utilization of magnetorheological dampers for vibration control applications in complex structures. It aims at developing a reliable decentralized model to track and monitor the building structures and control them before the earthquake actions are encountered. This article develops a novel dynamically optimized and decentralized mechanism using the PID controller for the self-regulation of conventional PID controller-based method. The major goal of decentralization is to ensure that each of the subsystem is compatible with one another and can also work independently with a higher efficiency at the time of fault. The combination of decentralization and self-regulation is tested for a tall building structural model with 10 floors. The proposed approach is compared with the conventional PID based mechanism under the faulty condition in order to illustrate its dynamism and usefulness for practical implementation. The proposed simulated model provides 95.54 % earthquake tracking precision and can be used for developing the earthquake protective schemes for the adequate survivability of tall building structures as well as to safeguard the human occupant in it.